Variations in mineral abundance within a single horizontal well path in the Woodford Shale, Arkoma Basin, Oklahoma - Wehner, Tyrel David (Kansas State University, 2018)
The Woodford Shale (Oklahoma, U.S.A.) is a prolific unconventional hydrocarbon resource. The Woodford has been shown to be heterogeneous in many geochemical, mineralogical, and rock mechanic properties across the state of Oklahoma, which presents a challenge to successful exploitation of this resource (Caldwell, 2014; Turner et al., 2015; Wiley, 2015; Zhang et al., 2017). Most prior studies of the Woodford Shale report properties from a single sample collected from a vertical well, which reports these values as a single point source on a distribution map. Studies using outcrop localities report lateral variations in several rock properties of the Woodford, but are limited to the short distances an outcrop provides (Turner et al., 2015). The main focus of this research is to determine whether rock properties important to the productivity of the Woodford Shale vary across a lateral well bore within the Woodford shale. Measurements of chemical and mineralogical compositions were performed on rock cutting samples from a single horizontal well path of the Carleigh 6H-32 across approximately one mile. The mineral makeup was determined by use of X-ray diffraction (XRD) and elemental concentrations were determined by hand-held X-ray fluorescence (HHXRF). What was found is that the Upper and Middle Woodford Shale are relatively homogeneous laterally. The lack of variation means that it’s possible to determine from which subgroup samples may have been taken. The geochemical data were used to calculate a mineral-based brittleness index (Wang and Gale, 2009), which was compared to the measured frack gradient across perforations of the Carleigh 6H-32 well. In addition, the total organic matter content (TOC) was approximated in the same samples using loss on ignition (LOI) methods. The calculated mineralogy within samples assigned to the Middle Woodford show some variability throughout the horizontal well, which leads to an associated variation in mineral brittleness index when using the Wang and Gale (2009) formula. The mineral based brittleness index correlates with observed fracture gradient during well completion. This suggests that the tendency to fracture is also variable along the well path, which should be considered during design of the well completion.
Keywords: Woodford Shale; Horizontal well; Mineral abundance; Mineral brittleness index; Frack gradient